2021
DOI: 10.11591/ijphs.v10i1.20576
|View full text |Cite
|
Sign up to set email alerts
|

Quality of self-management among diabetes mellitus patient

Abstract: Diabetes mellitus is a chronic disease that has very high morbidity and mortality rate. This disease cannot be cured but can be controlled with good self-management. This research determined the quality of self-management of diabetics at community health centers in Padang City in 2019. This is a descriptive-analytic study with amount of samples 105 people with diabetes. Data collection was carried out from July to November 2019 at seven community health centers in Padang City, namely: Nanggalo, Lapai, Alai, An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, support was an essential part of successful self-care. 29 This study showed that patients who had family and community full support had the possibility of practising self-care management 1.19 and 1.03 times compared to those who didn’t have full support. This finding was supported by a study in Dander Health Center that patients who get full family support will benefit from their healthy development.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, support was an essential part of successful self-care. 29 This study showed that patients who had family and community full support had the possibility of practising self-care management 1.19 and 1.03 times compared to those who didn’t have full support. This finding was supported by a study in Dander Health Center that patients who get full family support will benefit from their healthy development.…”
Section: Discussionmentioning
confidence: 75%
“…Data analysis using thematic analysis [23], [28], [29]. Data were analyzed using a thematic analysis approach [30], [31], by specifying coding [32], [33], make a similar patterns (pattern mathing), drawing and make major deductions [34], [35]. Peer-d briefings were also conducted to maintain the consistency of the informant's answers [36].…”
Section: Discussionmentioning
confidence: 99%
“…T2DM is a disease that cannot be cured but can be lowered by self-management. One management is by consuming food with bioactive compounds that affect antidiabetic properties [72]. Analog rice from various local sources is proven to contain nutritional compounds that have antidiabetic properties and can lower the risk of T2DM by consuming it adequately.…”
Section: Nutritional Compounds' Mechanismsmentioning
confidence: 99%